2017
DOI: 10.13057/biodiv/d180216
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Cytological studies on black orchid hybrid (Coelogyne pandurata Lindley)

Abstract: Abstract. Hartati S, Nandariyah, Yunus A, Djoar DW. 2017. Cytological studies on black orchid hybrid (Coelogyne pandurata Lindley). Biodiversitas 18: 555-559. Black orchid (Coelogyne pandurata Lindley) is one of the rare species of Coelogyne Lindley, protected by the government of Indonesia. The cytological character of orchid is very important to study to support the success of breeding. The study aimed to assess the chromosomal number, karyotype pattern and ploidy level the hybrid of Black Orchid (Coelogyne … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 9 publications
0
21
0
2
Order By: Relevance
“…Dendrogram shows that ten ISSR molecular markers are able to classify tree similarity clusters with a similarity coefficient of 0.51. The first cluster consisted of C. pandurata, C. rumphii, C. mayeriana, C. asperata, the second cluster was C. celebensis and the third was C. massangeana (Hartati et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dendrogram shows that ten ISSR molecular markers are able to classify tree similarity clusters with a similarity coefficient of 0.51. The first cluster consisted of C. pandurata, C. rumphii, C. mayeriana, C. asperata, the second cluster was C. celebensis and the third was C. massangeana (Hartati et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Orchidaceae is one of the largest family of plants, consisting of more than 25,000 species. Orchids are recognized as economically important commodities in the international flower industry, either as cut flowers or potted plants (Chase 2005;Hartati et al, 2017;Kuehnle, 2007). In adition to being used as an ornamental plant, several types of orchids have also been used as food or medicine (Luo et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Based on ISSR markers, C. pandurata and C. rumphii have the closest genetic relationship that is 70%. Additionally, cytological studies have shown that the karyotype of C. pandurata is 2n=56, C. rumphii is 2n=72 and their hybrid is 2n=54 (Hartati et al 2017). A second study showed that based on the morphological identification of these two species, they have a morphological similarity of 87% (Hartati et al 2019a).…”
Section: Introductionmentioning
confidence: 99%
“…The 2n range from 28 in Canthigaster coronata (Vaillant & Sauvage, 1875) (Arai 2011) to 46 chromosomes in the genus Sphoeroides anonymous, 1798 (Brum et al 1995, Brum 2000, Sá-Gabriel and Molina 2005, Alves et al 2008). Shape, size, and number of chromosomes of each species are always fixed, so knowledge about the karyotypes can be used for studies in taxonomy, diversity, kinship, and evolution, even though in certain circumstances also variations have been reported (Hartati et al 2017). To identify intra-and inter-specific variants karyotyping combined with molecular cytogenetic analyses are the methods best suited here.…”
Section: Introductionmentioning
confidence: 99%